Managing epilepsy by modulating glia - (:unkn) unknown (My University, 2016)
0

Antiepileptic drugs suppress epileptic seizures and provide a symptomatic control of seizures rather than anti-epileptogeniceffects. Evidence about links between glial functions and neuronal signaling has been accumulating and has opened a perspective for the development of anti-epileptogenic approaches for the management of convulsive and non-convulsive formsof epilepsy. Astrocytic excitability and glial transmission have been shown to play critical roles in epileptogenesis and seizuregeneration. Although glial cells in convulsive types of epilepsy have been widely studied, little work has been done on thecontribution of these cells in the non-convulsive epilepsy forms, particularly in absence epilepsy. This review underlies theparticipation of reactive astrocytes, glia modulating approaches and the roles of inflammatory cytokines in the modulationof convulsive and non-convulsive forms of epilepsy. The understanding of links between astrocyte functions and neuronalsignaling in epileptogenesis will be one of the top epilepsy research advances in the future.
Keywords: Anatomi ve Morfoloji